PLAN DE NEGOCIO PARA LA IMPLEMENTACIÓN DE PRODUCTOS TURÍSTICOS EN LA FINCA “DELITA” DE LA PARROQUIA GONZANAMÁ, CANTÓN GONZANAMÁ, PROVINCIA DE LOJA - DELGADO BRAVO, RODRIGO RAFAEL (2019)
Ecuador has countless areas of great tourist attraction that stand out for their varied culture and great biodiversity. The need to carry out this research is because despite the privileged location of the farm it is not yet developed in a tourist way, this is due to a lack of adequate infrastructure, which is why this proposal to carry out a "Plan" is carried out of Business for the Implementation of Tourist Products in the "DELITA" Estate of Gonzanamá Parish, Gonzanamá Canton, Loja Province ". For the development of the research work entitled: "Business Plan for the Implementation of Tourism Products in the" DELITA "Estate of Gonzanamá Parish, Gonzanamá Canton, Loja Province", it is considered as a general objective to prepare a Business Plan, for the implementation of tourism products for the “DELITA” farm of Gonzanamá Parish, Gonzanamá Canton, Loja Province; from which three specific objectives are derived, the first focused on making a tourist diagnosis of the current situation of the "DELITA" estate of the Gonzanamá Parish where it is known to know the internal situation of the farm; the second was to propose a Business Plan for tourism products of the Finca “DELITA” of the Gonzanamá Parish; which was developed through the business idea, market research and business organization; The third is to propose the strategies for the implementation of the Tourism Products Business Plan at the Finca “DELITA of the Parroquia Gonzanamá, which is managed through the financial study. The methodology used was based on the deductive method which helped in the investigation for the diagnosis, inductive method was used to generalize the factors and data contemplated, descriptive method this method was applied to investigate data and characteristics of the general population within of the field of study, analytical method that allowed to know more the place of study, whose analysis will be used to perform the SWOT matrix and the strategies matrix. As a result of the tourism diagnosis, four strategic objectives were obtained, which were developed in the business plan proposal. In the first objective, the tourist package was prepared in order to enhance the existing attractions within the Estate where the itinerary was designed and the package budget will be included; The second objective is to implement the restoration service in order to promote the development of tourism activity on the farm and the products produced therein; The third objective is to carry out the promotion and dissemination of tourism to publicize the Finca “DELITA” on the market. The internet was used as a means of dissemination, websites were created and are part of the most used social networks today (Facebook, Instagram) within these spaces the spaces with which the farm has will be announced; The fourth objective is to implement 5 the recreation service (swimming pool) to thereby promote tourism development and provide additional services where visitors can get distracted. Finally, the respective conclusions and recommendations of the work carried out were established, most of them are directed to the owner of the Estate and to the GAD of Gonzanamá, in terms of the competences and training that should be taken. After having developed the research project, it is concluded that the execution of tourist activities in the “DELITA” Farm, from a technical, administrative and financial point of view, is viable and profitable because the capitals with which it will work will be feasible according to the financial analysis developed in the time the project will be developed, so it is recommended that the various institutions support this initiative since it will generate new jobs and improve the quality of life of the population.